2002
DOI: 10.1016/s0092-8674(02)00623-2
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibition of c-Abl

Abstract: Despite years of investigation, the molecular mechanism responsible for regulation of the c-Abl tyrosine kinase has remained elusive. We now report inhibition of the catalytic activity of purified c-Abl in vitro, demonstrating that regulation is an intrinsic property of the molecule. We show that the interaction of the N-terminal 80 residues with the rest of the protein mediates autoregulation. This N-terminal "cap" is required to achieve and maintain inhibition, and its loss turns c-Abl into an oncogenic prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(181 citation statements)
references
References 42 publications
5
172
1
3
Order By: Relevance
“…Constitutively active c-Abl (Δ1-81 c-Abl) 28 Consistent with previous studies, 18 when overexpressed in MCF10A cells, YAP induced EMT, as evidenced by a fibroblast-like appearance and a dispersed cell distribution on a regular culture dish (Figure 2d, left panels). In contrast, MCF10A cells expressing YAP in the presence of active c-Abl displayed a cobblestone appearance similar to the control MCF10A cells.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Constitutively active c-Abl (Δ1-81 c-Abl) 28 Consistent with previous studies, 18 when overexpressed in MCF10A cells, YAP induced EMT, as evidenced by a fibroblast-like appearance and a dispersed cell distribution on a regular culture dish (Figure 2d, left panels). In contrast, MCF10A cells expressing YAP in the presence of active c-Abl displayed a cobblestone appearance similar to the control MCF10A cells.…”
Section: Resultssupporting
confidence: 90%
“…18 c-Abl and Abl-PP), 28 and nuclear c-Abl, bearing no nuclear export signal (NES mutant c-Abl). 29 These results suggest that c-Abl inhibits YAP in coactivating TEAD, in EMTand enhanced migration induction, and in transforming MCF10A cells.…”
Section: Resultsmentioning
confidence: 99%
“…The plasmids used were: pCDNA Flag-Yap1, 21 pSLX c-Abl WT and pSLX c-Abl D1-81, kindly provided by G Superti-Furga. 33 pCDNA c-Abl D1-81 was sub-cloned from pSLX c-Abl D1-81, and Flag-c-Abl D1-81 was constructed by inserting a Flag tag at the N-terminus of the construct. pSG5-c-Abl wt and kinase mutant are described in Agami et al 20 The 1b isoform was used for generation of full-length c-Abl constructs, and the numbering of c-Abl residues refers to positions in the 1b isoform.…”
Section: Methodsmentioning
confidence: 99%
“…173 For example, the cellular form of the Abelson leukemia virus tyrosine kinase (c-Abl) is a large protein that consists of ~1150 residues whose N-terminal half includes an N-terminal "cap" of ~80 residues that is important for autoinhibition followed by an SH3 domain, an SH2 domain, and a tyrosine kinase domain. 174 The analysis of the c-Abl kinase crystal structure revealed that there is no clearly interpretable electron density for the ~80 residue N-terminal cap region. 175 Although SH3 domain possesses a characteristic fold consisting of five or six β-strands arranged in a form of two tightly packed anti-parallel β sheets, with the linker regions containing short helices, 173 it has been pointed out that extensive flexibility is necessary for target recognition.…”
Section: Intrinsic Disorder Protein Domains and Functionsmentioning
confidence: 99%